(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Water quality is one of the important factors in the shrimp culture activity. In shrimp culture ponds water quality is influenced by both environmental and management practices. In this context the water quality parameters and Vibrio loads both in control and experimental ponds were analyzed over a period of two years in Penaeus vannamei culture farms located at Ampalam of Srikakulam District, Andhra Pradesh, India, over a period of two consecutive years i.e 2018-2019. As most of the shrimp culture farming shifted from Penaeus monodon to P. vannamei culture system, limited studies are available on the water quality, and vibrio loads in P. vannamei culture system. It is evident from the study findings that the water quality parameters in the experimental ponds in the culture of P. vannamei showed that the pathogenic bacterial loads are totally in control in the ponds where the probiotics were administered and in those control ponds where there is no probiotic application, the pathogenic bacterial loads were increased during the entire culture period in both seasons of the study period.